Legal Protection of Pregnant Women Patients Abandoned by Health Workers - Pradila, Yudhistira Adi; Marlina, Tina; Maulida, Irma (Rechtsnormen: Journal of Law, 2024)
Background. Health is an integral part of daily life, from birth to death, and is supported by various health workers in specific fields such as doctors, midwives, and pharmacists. Despite the availability of health facilities, cases of patient abandonment by health workers, particularly involving pregnant women, have been reported. Purpose. This research aims to investigate one such case, focusing on the legal protection available for pregnant women patients abandoned by health workers, specifically midwives. The study also explores the legal actions that can be taken against the midwife responsible for abandoning the patient. Method. The research employs a legal analysis method by examining relevant laws and regulations governing health workers and midwifery, focusing on patient rights and professional obligations. It further examines ethical standards and legal consequences in such cases. Results. The findings reveal several potential factors contributing to the abandonment case, including negligence and gaps in the enforcement of professional responsibilities. The results serve as a valuable resource for educating health workers, particularly midwives, about the legal and ethical dimensions of their profession. This study emphasizes the importance of understanding the professional code of ethics, legal sanctions, and patient rights to prevent future occurrences of patient abandonment.   Conclusion. In conclusion, strengthening legal frameworks and ethical standards is critical to ensuring pregnant women receive adequate care and protection.